“A gente sabe fazer, mas colocar no papel é difícil”: construção de um manual de procedimentos como mediador para promoção à saúde no trabalho de atendentes. - da Silva, Nayana Rios Nunes (2023)
Public service activities are complex, despite appearing deceptively simple. They require various skills from workers to reconcile the interests of users, the institution, and themselves as individuals. Consequently, numerous studies in the field of psychology have highlighted the detrimental impact of customer service roles on the health of workers. Building on this understanding, this study aimed to analyze the constraints on the agency of workers in the public service sector of a Water and Sewage Autonomous Service in a city located in the interior of Ceará, Brazil. To achieve this goal, theoretical and methodological support was sought from Yves Clot's Activity Clinic, which stands out among work clinics for its interventional nature and its potential to bring about a change in the position of workers within the organizational context. The study unfolded in two stages, starting with intervention and followed by data analysis. The research was grounded in a qualitative approach, and the material generated during the intervention underwent constructive-interpretative content analysis by González Rey. Guided by this approach, a Standard Operating Procedure Manual for public service was developed, facilitating reflections on the profession based on the interactions of service providers with their work collective, with the providers being the protagonists of the entire process. Ten meetings were conducted weekly during workers' business hours, each lasting an hour and a half. The manual construction followed several steps, with service providers categorizing work processes, and the prescription of services being developed in pairs during each meeting, presented, discussed, and validated in the following session. Ultimately, the information was synthesized into an e-book and made available to management and workers. As a result, a document was produced that will guide the work of current service providers and serve as guidance for future professionals entering the sector. Additionally, during the meetings, participants were able to discuss the activity, clarify doubts, exchange ideas, and share strategies on how to perform their work, especially in facing the main challenges of their professional lives. In this way, the professional genre was revitalized, and agency was expanded, creating conditions that promote well-being and quality of life at work instead of leading to supposed illnesses